Seasonal Dynamics of Sand Flies (Diptera, Pshycodidae), Vectors of Cutaneous Leishmaniasis, in the City of Fez, Northern Morocco - Najoua Darkaoui; Abdellatif Janati Idrissi; Fatima Zahra Talbi; Youness El Fattouhi; Hajar El Omari; Mohamed Najy; Abdelkarim Taam; Abdellatif Alami; Fouad El-Akhal; Abdelhakim El Ouali Lalami (The Scientific World Journal)
The infections transmitted by sand flies (Diptera, Psychodidae) pose always a real health problem due to the increasing number of cases detected each year and the annual emergence of new leishmaniasis outbreaks. This study evaluated the temporal evolution of six species of sand flies in five stations inventoried between May 2017 and April 2018, in order to determine for the first time the extent of cutaneous leishmaniasis (CL) transmission in the city of Fez. The monthly impact of Fez sand fly density has been studied using all multivariate statistical analyses, including multiple factor correspondence analysis (MCA), which were performed using XLSTAT and the version of SPSS 20.0 test. Differences between concentrations were considered significant if P<0.05. To better study the results obtained, different ecological indices have been studied. This study showed that these vectors developed in different sectors of the city of Fez. A total of 816 sand flies were collected from five stations in the city, belonging to three species of the genus Phlebotomus (46.82%) and three species of the genus Sergentomyia (53.18%). The seasonal fluctuation of the average density followed a bimodal evolution for the three stations Dhar Richa, Ain Nokbi, and Boujloud. The stations of Ain Nokbi (0.87 ph/m2) and Dhar Richa (0.467 ph/m2) exposed the sites to a high average density with a maximum peak during August (1.965 ph/m2) and July (1.87 Ph/m2), respectively. S. minuta (44.24%), Ph. sergenti (26.96%), Ph. perniciosus (10.78%), and Ph. papatasi (9.07%) were the most qualified species. The calculated P value is above the 5% significance level, so the relative abundance of these species between study sites shows no significant difference. The period of phlebotomy activity of the genus Phlebotomus in Fez lasts seven months from May to November with a bimodal or trimodal evolution and varies according to the species or the surveyed station. The seasonal fluctuation of sand flies could be conditioned by climatic factors where the period of activity of the species coincides with the hot months (May, June, July, and August). We have observed that the temperature factor favors the prevalence of sand flies, while the difference in the relative abundance of species between the sites is related to the difference in the bioecological conditions of each site.